Johdanto - Hautala-Hirvioja, Tuija; Kyläniemi, Hanna; Mäkikalli, Maija; Pietarinen, Heidi (Matkailututkimus, 2022)
The Faculty of Arts and design at the University of Lapland in Rovaniemi Finland, and the RegionalMuseum of Lapland decided together to organize an international conference Souvenirsin Motion: Cultural and Historical Perspectives on the Souvenir as a Research with the support ofthe Finnish Cultural Foundation. The reason for organizing the conference was the observationthat there is very few research on souvenirs in Finland. There are many souvenirs related toLapland tourism in the collection of the museums, especially in the Regional Museum of Lapland.The conference was originally supposed to be in Rovaniemi in April 2020, but due to thecovid-19 pandemic, it was postponed for one year. In the end, the conference was held onlinefrom 22 April to 23 April 2021. The conference was well received and there were about 120 participants.The conference included five keynote presentations and nine inspiring and versatileparallel sessions (c.f. Karikko in this issue). Souvenirs proved to be diverse and contain manymeanings. The articles of this publication are associated with the conference. The Faculty of Arts and Design at the University of Lapland in Rovaniemi Finland, and the Regional Museum of Lapland organized an international conference Souvenirs in Motion: Cultural and Historical Perspectives on the Souvenir as a Research Object with the support of the Finnish Cultural Foundation. The reason for organizing the conference was the observation that there is very few research on souvenirs in Finland. There are many souvenirs related to Lapland tourism in the collection of the museums, especially in the Regional Museum of Lapland. The conference was originally supposed to be in Rovaniemi in April 2020, but due to the Covid-19 pandemic, it was postponed for one year. In the end, the conference was held online from 22 April to 23 April 2021. The conference was well received and there were about 120 participants. The conference included five keynote presentations and nine inspiring and versatile parallel sessions (c.f. ...